Abnormal placental pathological findings and adverse clinical outcomes of oocyte donation. (November 2020) - Esteves, Ashley; Rozon, Chloé; Clancy, Jennifer; Liao, Yan; Wen, Shi WU.; Fung, Karen Fung-Kee.; El Demellawy, Dina
Abstract: We sought to assess chronic inflammatory responses in patients who achieved pregnancy by oocyte donation and non-oocyte donation-assisted reproductive technology and delivered at The Ottawa Hospital. Data describing maternal health, obstetrical outcomes, neonatal outcomes, and placental pathology were collected and analyzed from electronic medical records. An increased frequency of adverse obstetrical outcomes was observed. In the oocyte donation-assisted reproductive technology group, placental pathology data demonstrated increased frequency of fetal vascular malperfusion (p = 0.02) and placenta accreta (p < 0.001), representing a chronic inflammatory response. Placental pathology reflecting dysregulated immune processes and vasculopathy is associated with oocyte donation. Highlights: Malperfusion is common in oocyte donation assisted reproductive technology pregnancies. Chronic deciduitis occurs in oocyte donation reproductive technology pregnancies. Placenta accreta occurs in oocyte donation reproductive technology pregnancies. Increased frequency of preeclampsia and gestational diabetes in such pregnancies.